Molecular characterization and functional analysis of Japanese flounder (Paralichthys olivaceus) thbs2 in response to lymphocystis disease virus. Issue 93 (October 2019) - Guo, Yanan; Nan, Xingyu; Zhang, Xiaoyan; Wang, Guixing; Ren, Yuqin; Wang, Yufen; Fu, Yuanshuai; Hou, Jilun
Abstract: In mammals, a matricellular protein, thrombospondin 2 (Thbs2) has been reported to play important roles in modulating cell-matrix interactions, vascular integrity and thrombosis formation. However, the role of gene, thbs2 has not yet been studied in teleost. In the present study, this novel fish gene from Japanese flounder was cloned and its function in resistant to lymphocystis disease virus was elucidated. The Japanese flounder thbs2 encoded a 1176-amino acid protein with 91% identity to medaka. Amino acid sequence indicated that Japanese flounder Thbs2 contained 10 typical conserved domains. The thbs2 was expressed in all stages of embryo development, and in hatched larva stage, its expression was significantly higher than that in other stages ( P  < 0.05). The relative expression level of thbs2 was significantly higher in the head kidney, liver, blood, gill, and heart of the lymphocystis disease virus resistant fish than in sensitive fish ( P  < 0.05); and in muscle, this difference was at highly significant ( P  < 0.01). Additionally, the distribution of Thbs2 in tissue was evaluated by immunohistochemical staining. Subcellular localization analysis showed that Thbs2 was distributed throughout the cytoplasm of the cells. Taken together, our results provide new basic data for thbs2 function, especially its role in anti-lymphocystis disease virus immune response. Highlights: The thbs2 was cloned and characterized in Japanese flounder. The highest expression of thbs2 in embryo appeared in hatched larva stage. The highest tissue expression of thbs2 was in muscle of LCDV-resistant fish. Thbs2 was a cytoplasmic protein.